[Go-Far 2016] - Chong, Kai Yan (2016)
A series of 8 videos, 60 seconds each. [1] Football Fans at Rah Aahan Stadium, Tehran (Video by Nicholas Tan & Samuel He). 2nd division players, 1st class supporters. -- [2] Tehran's Popular Skate Park (Video by Chong Kai Yan & Pang Xue Qiang). Meet the cool kids of Tehran. -- [3] 3. Life at Tehran University (Video by Asyraf Kamil & Sherry Wong). When Amin meets Maryam... -- [4] The Great Kickboxer of Iran (Video by Clifford Lee & Nicholas Tan). This Iranian kickboxer packs a punch. -- [5] Tehran's "Official" Currency Bazaar (Video by Emily Joosten & Liew Yu Wei). There's more than just jewellery, carpets and spices at Tehran's Grand Bazaar. -- [6] Hesham and His Two Parakeets (Video by Louisa Tang). Find your destiny with the help of 14th-century Persian poet Hafez - and a bird. -- [7] Preparing for a Religious Procession in Yazd, Iran (Video by Jim Chan). Deep inside Yazd's old town, men lift elaborate structures to show their faith. -- [8] Iranian Beryani Has No Rice (Video by Clifford Lee). Did you know biryani, a popular Indian rice dish, has origins in Iran? The name can be traced to the original Persian "birinj biriyan" - which literally means fried rice. But in Iran, the dish actually contains no rice.